(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses various aspects of educational interaction that have attracted the attention of researchers for many decades. In particular, the ways of organizing pedagogical interaction and their impact on the educational process and its participants are considered.